Ileo-caecal Tuberculosis Associated with Hepatic Involvement - A Case Report - Begum, SMK Nahar; Hoque, M Azizul; Rahmen, K Khalilur; Pramanik, AK; Alam, S Shafiqul (TAJ: Journal of Teachers Association, 2009)
This is the case history of a 36 year old male who presented with fever, diarrhoea, weight loss with tenderness in the right hypochondrium and right ileac region. This was finally diagnosed as an interesting case of ileo-caecal tuberculosis with associated hepatic involvement. doi: 10.3329/taj.v20i1.3093 TAJ 2007; 20(1): 60-63